Genetic analyses reveal panmixia in Indian waters and population subdivision across Indian Ocean and Indo-Malay Archipelago for Decapterus russelli - Anjaly Jose; Sandhya Sukumaran; Subal Kumar Roul; P. Abdul Azeez; Shoba Joe Kizhakudan; Neenu Raj; K. Nisha; A. Gopalakrishnan (Scientific Reports, 2023)
Abstract The Indian Scad, Decapterus russelli is an important pelagic carangid widely distributed throughout the Indian Ocean and the Indo-West Pacific. Despite being widely distributed in the Indian Ocean, the information regarding genetic structuring and diversity has been lacking compared to its Indo Malay Archipelago counterparts. The present study was conducted to investigate the genetic stock structure of D. russelli based on mitochondrial (Cyt b) and nuclear (DrAldoB1) markers along Indian waters. The results indicated the presence of a single panmictic stock across the Indian Ocean region. High haplotype diversity associated with low nucleotide diversity suggested a population bottleneck followed by rapid population growth. Phylogenetic analysis revealed the absence of geographical clustering of lineages with the most common haplotype distributed globally. The pelagic life style, migratory capabilities, and larval dispersal may be the contributing factors to the observed spatial homogeneity of D. russelli. However, significant genetic differentiation was observed between the populations from Indian Ocean and Indo-Malay Archipelago. Hierarchical molecular variance analysis (AMOVA), pairwise FST comparisons and SAMOVA showed existence of two distinct genetic stocks of D. russelli in the Indian Ocean and IMA. The observed interpopulation genetic variation was high. A plausible explanation for the genetic differentiation observed between the Indo-Malay Archipelago and the Indian Ocean regions suggest the influence of historic isolation, ocean surface currents and biotic and abiotic features of the ocean. Also, there was a significant relationship between genetic distance and geographical distance between population pairs in a manner consistent with isolation-by-distance. These resulted in the evolution of a phylogeographic break for this species between these regions. The findings of these results suggest that D. russelli from the Indian Ocean shall be managed in its entire area of distribution as a single stock. Further, the Indian Ocean and Indo-Malayan stocks can be managed separately.